Giant ice rings in southern Baikal: multi-satellite data help to study ice cover dynamics and eddies under ice - Kouraev, Alexei V.; Zakharova, Elena A.; Kostianoy, Andrey G.; Shimaraev, Mikhail N.; Desinov, Lev V.; Petrov, Evgeny A.; Hall, Nicholas M. J.; Rémy, Frédérique; Suknev, Andrey Ya (The cryosphere, 2021)
Ice cover on lakes is subject to atmospheric forcing from above and the influence of water dynamics and heat flux from below. One characteristic example of these influences in some large lakes, such as Lake Baikal in Russia, are the giant ice rings and the associated eddies under the ice cover. In April 2020 a giant ice ring appeared in southern Baikal, and a lens-like eddy was detected below the ice. We analysed the temporal changes of ice cover using satellite images from multiple satellite missions – MODIS on Terra and Aqua, Sentinel-1 SAR, Sentinel 2 MSI, Landsat 8, PlanetScope, satellite photography from the International Space Station, and radar altimetry data from Jason-3. Satellite imagery and meteorological data show unusual temporal changes of ice colour in April 2020, which were explained by water infiltration into the ice followed by the competing influences of cold air from above and the warm eddy below the ice. Tracking of ice floe displacement also makes it possible to estimate eddy currents and their influence on the upper water layer. Multi-satellite data contribute to a better understanding of the development of ice cover in the presence of eddies, the role of eddies in horizontal and vertical heat and mass exchange, and their impact on the chemistry and biology of the lakes and on human activity.